2020
DOI: 10.3390/ani10061095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Proportions Determined by Mid-Infrared Spectroscopy and Gas Chromatography in Bulk and Individual Milk Samples

Abstract: Rapid analytical methods can contribute to the expansion of milk fatty acid determination for various important practical purposes. The reliability of data resulting from these routine methods plays a crucial role. Bulk and individual milk samples (60 and 345, respectively) were obtained from Czech Fleckvieh and Holstein dairy cows in the Czech Republic. The correlation between milk fatty acid (FA) proportions determined by the routine method (infrared spectroscopy in the mid-region in connection with Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The use of different analytical methods might also be a crucial factor. Samková et al (2020) recently showed that the FT-IR method can be advantageously used, especially for those FA and FA groups that are present in high proportions of the total milk fat. Results for FA present in milk in low proportions should, however, be interpreted with caution, because of lower correlation coefficients between FT-IR and GC values for these traits.…”
Section: Discussionmentioning
confidence: 99%
“…The use of different analytical methods might also be a crucial factor. Samková et al (2020) recently showed that the FT-IR method can be advantageously used, especially for those FA and FA groups that are present in high proportions of the total milk fat. Results for FA present in milk in low proportions should, however, be interpreted with caution, because of lower correlation coefficients between FT-IR and GC values for these traits.…”
Section: Discussionmentioning
confidence: 99%
“…Given the association of HYK with energy balance, it is also important to consider milk components which greatly influence milk energy output. Specifically, milk fat represents half of the energy in milk [ 25 ] and the profile of FA within the milk can shed light on the source of milk fat [ 26 , 27 ]. Milk fat percent is commonly reported as being greater in cows with HYK [ 16 , 17 , 23 , 28 ], consistent with the data presented herein.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the FAs was performed on a Varian 3800 instrument (Varian Techtron, Palo Alto, CA, USA). The identification of FAs in the milk fat was performed using Supelco standards according to Samková et al [ 22 ]. The FA proportions were stated as g/100 g of FAs.…”
Section: Methodsmentioning
confidence: 99%